Some Iranian Horse Names in “Shahnameh” by Ferdowsi - Khachatryan, Zaruhi (Bulletin of Yerevan University B: Philology, 2024)
The horse has an exceptional role and significance in the life and culture of Iranian peoples. “Shahnameh”, the masterpiece of the great poet of Iran, Ferdowsi, is considered as an endless source and a powerful potential for the development of the Persian language thanks to its highly rich vocabulary. A big and unique part of the vocabulary is the words related to the animal world, where the horse names have a special place among the names of domestic animals. Ferdowsi in “Shahnameh” uses more than thirty terms indicating horses, as a mean of military actions, as a domestic pack animal and as a vehicle, as well as horse names based on the physical and appearance features. In this article some of the Iranian horse names (asb, čarme, bur, tāzi, tak, takāvar, xeng,raxš/Raxš, samand/ Samand, sīyāh/ Sīyāh) are discussed from the morphological and etymological perspectives.
Keywords: Ferdowsi; Shahnameh; horse; horse name; word meaning; origin; protoform; dictionary